UPAYA MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK MELALUI PENERAPAN MODEL PEMBELAJARAN CONNECTING ORGANIZING REFLECTING EXTENDING - Shintia Fitriani (Jurnal Edukasi dan Penelitian Matematika, 2018)
One of coginitive competence that wished to be owned by student is the understanding of mathematical concepts, butbased on the result of observation and given test show that learning activities and competence on understandingmathematical concept of students SMPN 30 Padang grade VIII are still low. One of the efforts to overcome thisproblem is by applying Connecting Organizing Reflecting Extending (CORE) learning model. The purpose of thisresearch were to describe student’s learning activities in grade VIII of SMPN 30 Padang during applied CORElearning model and describe whether student’s concept understanding using CORE learning model better thanstudent’s concept understanding using coventional learning model. Based on data analysis, obtained: (1) percentage ofstudent’s learning activities have fluctuated on some indicator activities that observed; (2) student’s conceptunderstanding using CORE learning model is better than student’s concept understanding using conventional learningmodelKeywords–CORE learning model, student’s learning activities , understanding of mathematical concept